Reviewing building construction statistics in Turkey: Stakeholders’ perspective - Yitman, İbrahim; Akiner, Ilknur; Marar, Khaled (Elsevier, 2012)
Construction is one of the industries of strategic economic importance. Governments using their national institutions are involved in the collection of economic statistics, which indicate the state of their economy in the form of an annual time series. However, the completeness and accuracy of these statistics is frequently questioned by the stakeholders within the sector. Therefore there is an increasing need for accurate, manageable and reliable statistics to enable sound analysis of the construction sector. The main purpose of this research is to review building construction statistics in Turkey. The objectives of the review are to 1) engage with users to ascertain their views on the statistics and to identify their needs, and 2) investigate whether the statistics in their present form continue to meet user needs, and identify options for change. As part of the review, a user consultation exercise is carried out to identify whether user needs are met by the statistics, as well as to ascertain users’ views on the European Statistical System (ESS) key dimensions of the quality of the statistics. This review of building construction statistics will facilitate statistical information to be presented in a more comprehensive manner, with sufficient detail, highly reliable in terms of quality and responsive to dynamic changes of the sector (such as inflation and structural adjustment policies).
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.habitatint.2011.12.002) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Building construction statistics; Construction industry; Turkey